RETRACTED: Innovative methods for substantiation of the final oil recovery recovery factor - Khayitov Odiljon; Umirzokov Azamat; Yusupkhojaeva Elleonora; Abdurakhmonova Surayyo; Kholmatova Nargiza; Akhmedova Nargiza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001